Genome mining approach for harnessing the cryptic gene cluster in Alternaria solani: production of PKS–NRPS hybrid metabolite, didymellamide B. Issue 25 (22nd June 2016) - Ugai, Takahiro; Minami, Atsushi; Gomi, Katsuya; Oikawa, Hideaki
Graphical abstract: Highlights: Heterologous production of fungal metabolite with 3 genes. Biosynthetic gene dependent production of fungal polyketide. Non-enzymatic [4+2] cycloaddition of highly reactive linear triene. endo -Selective Diels–Alder reaction generating trans -decalin with 2-pyridone. Abstract: Using a heterologous expression system in Aspergillus oryzae we characterized cryptic biosynthetic genes found in Alternaria solani . This system enabled the isolation of an antifungal metabolite, didymellamide B, which was previously not detected in the extract of the A. solani . The co-production and chemical transformation of didymellamide congeners enabled us to decipher the biosynthetic pathway of didymellamide B as follows: (1) formation of a linear polyketide chain with 3-acyltetramate, (2) oxidative ring expansion to yield a 2-pyridone skeleton, and (3) non-enzymatic endo -selective [4+2] cycloaddition to afford a trans -decalin. These results demonstrate the robustness and reliability of the A. oryzae expression system.